La invención de la medicina. Hipócrates de Cos: su vida, su obra y su tiempo (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
I try to make a study of Hippocrates of Cos: his life, his work, and his time, emphasizing that he was the introducer of rational, scientific medicine in the western world. Hippocrates was a child of his time, and he was interested in the study of of Nature (Physis), in the use of reason (Logos), and in his interest in living and suffering humanity. His doctrine lasted for two millennia, until the Renaissance. Today, it is again rediscovered, due to the existential crisis of our medical care, and this has given rise to a medical and cultural regenerationist movement, called neo-hippocratism.
Keywords: Logos. Physis. Humoral theory. Health and disease.